The global and persistent millennial-scale variability in the thermoluminescence profiles of shallow and deep Mediterranean sea cores - Cini Castagnoli, G.; Bonino, G.; Taricco, C. (Societa italiana di fisica, 1998)
In this paper we present the thermoluminescence (TL) profile in the last 7500 y, measured in the upper part of the deep Tyrrhenian sea core CT85-5. This core was dated with tephroanalysis and radiocarbon techniques: a constant sedimentation rate (10 cm/ky) was found up to 200 cm. The sampling interval adopted for obtaining the TL profile is 2.5 mm, corresponding to 25 y. Using different spectral-analysis methods, we show the presence of a millennial-scale variability, corresponding to an average period of about 1315 y. This oscillation has been noted also in other climatic indices measured in North Atlantic sea sediment cores and in the Greenland GISP2 ice core. This result indicates that this millennial oscillation is the expression of climate changes of worldwide extent. We show that this millennial periodicity persisted during the last deglaciation. The transition to Holocene was determined in our core by the oxygen isotope ratio d 18O measured in Globigerina bulloides. The fact that the observed TL changes do not have a local character is also suggested by the excellent agreement between this deep sea TL profile of the uppermost part of the core and the TL profile measured in the shallow Ionian sea GT89-3 core over the last 2500 y, with a time resolution of 3.096 y.